Test performance and predictors of accuracy of endoscopic ultrasound-guided fine-needle aspiration for diagnosing biliary strictures or masses - Raine, Tim; Thomas, John P.; Brais, Rebecca; Godfrey, Edmund; Carroll, Nicholas R.; Metz, Andrew J. (Endoscopy International Open, 2020)
Background and study aims Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) has emerged as an important method for obtaining a preoperative tissue diagnosis for suspected cholangiocarcinoma. However, doubts remain about test sensitivity. This study assessed the value and limitations of EUS-FNA in clinical practice. Patients and methods Patients undergoing EUS-FNA for biliary strictures/masses at a UK tertiary referral center from 2005 to 2014 were prospectively enrolled. Data on EUS-FNA findings, histology, and endoscopy and patient outcomes were collected to evaluate test performance and identify factors predictive of an inaccurate diagnostic result. Results Ninety-seven patients underwent a total of 112 EUS-FNA procedures. Overall test sensitivity for an initial EUS-FNA for suspected cholangiocarcinoma was 75 % (95 % CI 64 %–84 %), with specificity 100 % (95 % CI 85 %–100 %) and negative predictive value 0.62 (95 % CI 0.47–0.75). Hilar lesions, the presence of a biliary stent, and a diagnosis of PSC were significantly independently associated with an inaccurate result. For the most difficult cases, repeat sampling and use of the Papanicolaou cytopathology grading scale led to an increase in test sensitivity from 17 % to 100 % (P = 0.015) with no loss of specificity. Conclusions EUS-FNA was found to be a useful method for obtaining a preoperative tissue diagnosis for patients with suspected cholangiocarcinoma. This study identified markers that can reduce test accuracy and measures that can improve test performance of EUS-FNA.